Rescue of Recombinant Adenoviruses by CRISPR/Cas-Mediated in vivo Terminal Resolution - Riedl, André; Fischer, Julian; Burgert, Hans-Gerhard; Ruzsics, Zsolt (Frontiers in Microbiology, 2022)
Recombinant adenovirus (rAd) vectors represent one of the most frequently used vehicles for gene transfer applications in vitro and in vivo. rAd genomes are constructed in E. coli where their genomes can be maintained, propagated and modified in form of circular plasmids or bacterial artificial chromosomes. Although the rescue of rAds from their circular plasmid or bacmid forms is well established, it works with relatively low primary efficiency, preventing this technology for library applications. To overcome this barrier, we tested a novel strategy for reconstitution of rAds that utilizes the CRISPR/Cas-machinery to cleave the circular rAd genomes in close proximity to their ITRs within the producer cells upon transfection. This CRISPR/Cas-mediated in vivo terminal resolution allowed efficient rescue of vectors derived from different human adenovirus (HAdV) species. By this means, it was not only possible to increase the efficiency of virus rescue by about 50-fold, but the presented methodology appeared also remarkably simpler and faster than traditional rAd reconstitution methods.